Educational Scenarios Using Remote Laboratory VISIR for Electrical/Electronic Experimentation - Castro, Manuel (2017)
In 2015, Electrical and Computer Engineering Department (DIEEC) of the Spanish University for Distance Education (UNED) in Spain started to- gether with the Santiago del Rosario National University (UNSE, Argentina) and with the support of the Research Institute of Education Sciences of Ro- sario (IRICE-CONICET, Argentina) under the Coordination of the Polytechnic Institute of Porto (IPP, Portugal) the new development and deployment of the VISIR system inside the UNSE University as part of the VISIR+ Project. The main objective of the VISIR+ Project is to extend the current VISIR net- work in South America, mainly in Argentina and Brazil, with the support and patronage of the European Union Erasmus Plus program inside the Capacity Building program and as part of an excellence network future development in- tegration framework. This extension of VISIR nodes reconfigure in 2016 a new project, PILAR, that as part of the Erasmus Plus projects will allow the Strategic Partnership to develop a new federation umbrella over the existing nodes and network.